Determining the impact of Covid-19 on the business norms and performance of SMEs in China. Issue 1 (31st December 2022) - Sun, Tiezhu; Zhang, Wei-Wei; Dinca, Marius Sorin; Raza, Muhammad
Abstract: This study's key purpose was to examine the impact of COVID-19 on SMEs' business norms and performance in China. The primary quantitative data have been collected through a survey questionnaire based on 330 participants. For analyzing the collected data, the use of the SEM technique has been made in this study. The researcher has adopted the data from the managers and employees belonging to the SMEs in China who are the research respondents. The data has been gathered from a sample size of 330. The number of distributed questionnaires was 340, whereas the responses gained were nearly 335, out of which 330 responses were selected. In the SEM technique, a CFA test was conducted to confirm the model's reliability and validity, whereas the results of path assessment were presented to examine the association between the variables. The findings of this study have confirmed the significant impact of COVID-19 on innovative operational procedures, profitability, remote work, and stakeholder satisfaction and safety.